Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Numbered Head Together di Sekolah Dasar - Agustia, Yolanda; Indrawati, Tin (Universitas Negeri Padang, 2023)
This research is motivated by the low learning outcomes of students in integrated thematic learning. The purpose of this study was to describe the increase in student learning outcomes in integrated thematic learning using the Numbered Head Together (NHT) Model in class V SD Negeri 23 Koto Tuo, Sungai Tarab District, Tanah Datar Regency. The research used is a type of classroom action research (CAR) using qualitative and quantitative approaches. Teachers and students in class V, totalling 16 students, were used as research subjects. This research was conducted in 2 cycles, in each cycle there were 4 stages, namely planning, implementing, observing and reflecting. The research findings can be seen in the characteristics of the Learning Implementation Plan, where cycle I obtained an average score of 85% (Good), and cycle II obtained an average score of 94.44% (Very Good). In the first cycle, the implementation of learning on the part of the teacher reached an average of 84.3% (Good) and increased to 93.75% in the second cycle (Very Good). The average value of the student component in cycle I was 84.3% (Good), and increased to 93.75% in cycle II (Very Good). The average student learning outcomes were 83.5 (Good) in Cycle I and 90.6 (Good) in Cycle II.